(untitled) (LEARNing Landscapes, 2018)
Teacher voices hold weight for their colleagues. When teachers tell a story of a positive experience with technology (or other teaching tools or strategies), they are showing that it is possible. “Stories, particularly those that are concrete and readily identified with, are particularly powerful for transferring knowledge rich in tacit dimensions” (Swap, Leonard, Shields, & Abrams, 2001, p. 105). When teachers share their stories with each other, they create a reality based on concrete possibility. This article will focus on how we use teacher stories and conversations in professional development (PD) to create positive realities for teaching and learning.